2018
DOI: 10.1016/j.scitotenv.2018.06.188
|View full text |Cite
|
Sign up to set email alerts
|

The cumulative impacts of small reservoirs on hydrology: A review

Abstract: The number of small reservoirs has increased due to their reduced cost, the availability of many favourable locations, and their easy access due to proximity. The cumulative impacts of such small reservoirs are not easy to estimate, even when solely considering hydrology, which is partially due to the difficulty in collecting data on the functioning of such reservoirs. However, there is evidence indicating that the cumulative impacts of such reservoirs are significant. The aim of this article is to present a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0
30

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 91 publications
(153 reference statements)
1
87
0
30
Order By: Relevance
“…At present, in some catchments the density of such small reservoirs may reach 10 reservoirs per km 2 [16], yet a systematic assessment of the global distribution of such an important class of small reservoirs remains lacking. With development of remote sensing techniques for retrieving salient information from satellite imagery [17][18][19], the identification of locations, sizes, and usage of small water reservoirs now becomes feasible.…”
Section: Introductionmentioning
confidence: 99%
“…At present, in some catchments the density of such small reservoirs may reach 10 reservoirs per km 2 [16], yet a systematic assessment of the global distribution of such an important class of small reservoirs remains lacking. With development of remote sensing techniques for retrieving salient information from satellite imagery [17][18][19], the identification of locations, sizes, and usage of small water reservoirs now becomes feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors that addressed this issue in semi-arid regions [31,34] found extraordinarily high values of seepage rates (up to 80 mm/day) that led the ponds to keep water only for short periods of time, which questions their usefulness. Nevertheless, these seepage rates contrast to regular values reported for this type of pond, which rarely exceed 5 mm/day [11,35,36]. Therefore, there is limited knowledge about the effectiveness of these ponds operating under normal conditions.In this study, the structural and functional attributes of a sample of representative livestock watering ponds in the southwest of the Iberian Peninsula and the temporal patterns of their water regime were investigated, with the objectives (1) to determine the influence of temporal rainfall variability on water availability in the ponds; (2) to assess the capacity of the ponds to conserve stored water (i.e., their effectiveness) during the regular dry season and during drought events; (3) to examine the influence of factors such as pond size and catchment area on the effectiveness of the ponds; and (4) to test whether simple analyses, primarily based on precipitation data and aerial photographs available from public sources, can be used reliably in these and other rangeland areas to suggest minimum values for the above factors, which can serve as a guide for the design of watering ponds.It is expected that the conclusions of this study may be helpful for a better understanding of the hydrological behavior of watering ponds of Iberian rangelands, as well as the factors that determine their efficiency in terms of water supply.…”
mentioning
confidence: 68%
“…Some authors that addressed this issue in semi-arid regions [31,34] found extraordinarily high values of seepage rates (up to 80 mm/day) that led the ponds to keep water only for short periods of time, which questions their usefulness. Nevertheless, these seepage rates contrast to regular values reported for this type of pond, which rarely exceed 5 mm/day [11,35,36]. Therefore, there is limited knowledge about the effectiveness of these ponds operating under normal conditions.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Although the impacts of on-farm storage are not considered in their study, the authors suggest that their assessment could be helpful in comparing the storage potential of large reservoirs with on-farm storages. Habets et al (2018) review modelling approaches to assess the hydrologic impacts of small reservoirs. As their focus is on modelling river flow, they relate to water extraction for irrigation as an exogenous factor.…”
Section: Literature Reviewmentioning
confidence: 99%